ANALISIS PERENCANAAN PAJAK TERHADAP PENYUSUTAN PADA PT.X - Maksalmina Maksalmina (Jurnal Akuntansi Muhammadiyah (JAM), 2022)
This research was conducted at PT. X which is domiciled in Banda Aceh, with the aim of knowing what depreciation methods can be used to minimize the company's tax burden and the impact it has. The data used is secondary data collected through documentation of financial statements for 2021 which includes data on the list of company fixed assets for 2021. This research is included in the type of descriptive qualitative research by collecting facts and identifying data that focuses on depreciation of fixed assets. Based on the research results, it was found that tax planning shows an effort to minimize the tax burden through the depreciation step using the declining balance method as a depreciation calculation. The conclusion of this study by recalculating depreciation using the declining balance method can save the tax burden that must be paid by the company